Mathematical modeling for the technological process of surface soil compaction by the inertial vibratory rammer - Ivanchuk, Yaroslav (Academic journal Industrial Machine Building Civil Engineering, 2019)
The high efficiency of the technological process of surface soil compaction using vibration and vibro-impact treatment has been determined. High degree intensification of the soil compaction process is achieved by using original inertial vibratory rammers with a hydro-pulse drive. A new mathematical model has been developed for the surface soil compaction processes study by the inertial vibratory rammers. Using numerical modeling, work dependencies are obtained to determine the main operating characteristics for the technological process of surface soil compaction by inertial vibratory rammers based on a hydro-impulse drive.